Power system relaying - Horowitz, Stanley H., 1925- (John Wiley and Sons, 2014)
The previous three editions of Power System Relaying offer comprehensive and accessible coverage of the theory and fundamentals of relaying and have been widely adopted on university and industry courses worldwide. With the third edition, the authors have added new and detailed descriptions of power system phenomena such as stability, system-wide protection concepts and discussion of historic outages. Power System Relaying, 4th Edition continues its role as an outstanding textbook on power system protection for senior and graduate students in the field of electric power engineeri.
Fourth edition.
Keywords: Protective relays.; Electric power systems -- Protection.; elektronické knihy; electronic books